Terapia cognitivo-comportamental on-line de sessão única para insônia: adaptação e viabilidade - Figueiredo, Laura Cesar (2023)
The dissertation's primary objective was to adapt a Cognitive-Behavioral Therapy (CBT) intervention for insomnia, specifically for online delivery in a single-session format, tailored to individual needs, and to assess its feasibility. Three studies were conducted to address the research question: "Is a single-session online CBT-I program a viable treatment option?" Study 1 entailed a systematic review of online CBT practices for insomnia, with the aim of comprehensively delineating the constituent components of this therapeutic approach. In Study 2, the adaptation of the intervention to an online, single-session format was executed, alongside the development of a Therapist Manual designed as a practical guide for professional implementation. Study 3 involved the application of the intervention that had been refined in Study 2, followed by an evaluation of its feasibility. The findings indicated that the online, single-session intervention exhibits potential as an accessible, scalable, and effective treatment modality. Nonetheless, it is imperative to emphasize the necessity for further investigations featuring larger sample sizes and comprehensive training for healthcare professionals to corroborate these promising outcomes.